RACK-1 Acts with Rac GTPase Signaling and UNC-115/abLIM in Caenorhabditis elegans Axon Pathfinding and Cell Migration - Demarco, Rafael S. (Public Library of Science, 2010)
Migrating cells and growth cones extend lamellipodial and filopodial protrusions that are required for outgrowth and guidance. The mechanisms of cytoskeletal regulation that underlie cell and growth cone migration are of much interest to developmental biologists. Previous studies have shown that the Arp2/3 complex and UNC-115/abLIM act redundantly to mediate growth cone lamellipodia and filopodia formation and axon pathfinding. While much is known about the regulation of Arp2/3, less is known about regulators of UNC-115/abLIM. Here we show that the Caenorhabditis elegans counterpart of the Receptor for Activated C Kinase (RACK-1) interacts physically with the actin-binding protein UNC-115/abLIM and that RACK-1 is required for axon pathfinding. Genetic interactions indicate that RACK-1 acts cell-autonomously in the UNC-115/abLIM pathway in axon pathfinding and lamellipodia and filopodia formation, downstream of the CED-10/Rac GTPase and in parallel to MIG-2/RhoG. Furthermore, we show that RACK-1 is involved in migration of the gonadal distal tip cells and that the signaling pathways involved in this process might be distinct from those involved in axon pathfinding. In sum, these studies pinpoint RACK-1 as a component of a novel signaling pathway involving Rac GTPases and UNC-115/abLIM and suggest that RACK-1 might be involved in the regulation of the actin cytoskeleton and lamellipodia and filopodia formation in migrating cells and growth cones.